2017
DOI: 10.1021/acs.jmedchem.7b00062
|View full text |Cite
|
Sign up to set email alerts
|

First Dual Inhibitors of Steroid Sulfatase (STS) and 17β-Hydroxysteroid Dehydrogenase Type 1 (17β-HSD1): Designed Multiple Ligands as Novel Potential Therapeutics for Estrogen-Dependent Diseases

Abstract: STS and 17β-HSD1 are attractive targets for the treatment of estrogen-dependent diseases like endometriosis and breast cancer. The simultaneous inhibition of both enzymes appears more promising than blockage of either protein alone. We describe a designed multiple ligand approach resulting in highly potent dual inhibitors. The most interesting compound 9 showed nanomolar IC values for both proteins, membrane permeability, and no interference with estrogen receptors. It efficiently reversed E1S- and E1-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Additionally, the development of dual/triple inhibitors, able to simultaneously target redundant intracrine pathways, is desirable. Several double STS‐aromatase inhibitors are under investigations , and very recently, the first dual 17β‐HSD‐1/STS inhibitor was developed .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the development of dual/triple inhibitors, able to simultaneously target redundant intracrine pathways, is desirable. Several double STS‐aromatase inhibitors are under investigations , and very recently, the first dual 17β‐HSD‐1/STS inhibitor was developed .…”
Section: Discussionmentioning
confidence: 99%
“…The IC50 values of the dual inhibitor 53 (figure 12) in intact T47D cells were 15 nM and 22 nM for STS and 17β-HSD1, respectively, and STS inhibition was found to be irreversible. The compound did not interfere with ERs but efficiently reversed E1S-and E1-induced T47D cell proliferation, without affecting E2-induced proliferation (Salah et al 2017).…”
Section: Dual Inhibitors Of 17β-hsd1 and Steroid Sulfatase (Sts)mentioning
confidence: 92%
“…Recently, the other enzyme implicated in the hormone biosynthesis process, 17b-HSD, has reached potential therapeutic importance in the treatment of hormone-dependent diseases. Salah et al 92 reported the first dual inhibitors of STS and 17b-hydroxysteroid dehydrogenase type 1 (17b-HSD1) as promising therapeutics for oestrogen-dependent diseases. The design of dual STS/ 17b-HSD1 inhibitors was based on combining structural elements, essential for 17b-HSD1 inhibition, with the sulphamate-aryl pharmacophore (crucial in STS inactivation).…”
Section: Multitargeting Agents With Sts Inhibitory Activitiesmentioning
confidence: 99%